Ceres. - Food and Agriculture Organization of the United Nations ([Rome, Food and Agriculture Organization of the United Nations], 1968)
"FAO review on development" (varies).
Keywords: Agriculture -- Developing countries -- Periodicals; Technical assistance -- Developing countries -- Periodicals; Food Supply -- Periodicals; International Cooperation -- Periodicals; Developing countries -- Rural conditions -- Periodicals